Effect of donor stimulation, frozen semen and heparin treatment on the efficiency of in vitro embryo production in goats - Kątska-Książkiewicz, Lucyna; Ryńska, Bożenna; Gajda, Barbara; Smorąg, Zdzisław (Theriogenology, 2004)
Investigations on in vitro embryo production in goats in comparison with other domestic species, especially cattle, have been the subject of few reports despite their usefulness for both basic research and commercial application. The objectives of this study were to compare the efficiency of IVP in goats using immature follicular oocytes recovered from FSH-primed and control goats. After IVM, oocytes were fertilized with fresh or frozen–thawed semen capacitated with or without heparin. Mature oocytes were fertilized in vitro with fresh and frozen–thawed sperm of a single buck. Sperm preparation included swim-up separation and heparin treatment (50μg/ml of sperm suspension for 45min) before spermatozoa were added to oocytes in TALP–IVF. After IVF, the zygotes were cultured for 24h and cleaved embryos were further cultured with goat oviduct epithelial cells or transferred to synchronized recipients. Mean number of oocytes recovered from FSH-primed goats (24.5±8.6) was significantly higher (P<0.01; t test) in comparison to control does (14.7±4.7). Irrespective of fresh or frozen semen, no differences were observed in blastocyst yield when sperm was treated with heparin. However, the highest cleavage rate (99/126; 79.4%) as well as blastocyst yield (47/126; 37.3%) was obtained after IVF with fresh sperm capacitated without heparin. Contrary to fresh sperm, heparin treatment of frozen–thawed sperm significantly improved (P<0.01) embryo cleavage. No differences between in vivo developmental competence of embryos related to sperm origin were found after transferring into recipients. Overall, more than 60% of the recipients became pregnant and 20% of all transferred embryos survived delivering 13 healthy kids. Our caprine IVP system allows obtaining embryos with developmental competence comparable to bovine IVP.